Identification of Candida Sp. Fungi in the Urine of Inpatient Surgical Patients Using Catheters at Bendan Regional General Hospital, Pekalongan City - Aulia Nada, Jingga; Riyanto, Agus (INDOGENIUS, 2025)
Background & Objective: andiduria is an opportunistic fungal infection caused by Candida sp. that indicates contamination, colonization, or infection that can be life-threatening and even fatal. This disease often affects hospitalized patients, especially those with severe underlying conditions. Patients at high risk of Candida sp. infection include those with compromised immune systems, often due to invasive procedures received during treatment. This study aims to determine the presence of Candida sp. in urine samples from surgical inpatients using catheters at Bendan General Hospital in Pekalongan City. Method: This study is a descriptive study using total sampling with 14 respondents. Result: Macroskopically, 5 samples tested positive for Candida sp. fungi, characterized by white-yellowish colonies, a slightly acidic odor, yeast-like colony shape, and a moist, convex colony surface. Following this, LPCB staining was performed on the 5 samples that were macroscopically positive for Candida sp. fungi. The positive samples were confirmed through microscopic observation using LPCB staining, showing oval-shaped yeast cells (blastospores) with a predominantly white color and a slight bluish tint. Conclusion: People who use catheters often forget to maintain hygiene to keep the pH stable, thereby minimizing the excessive growth of Candida sp. fungi. Risk factors that can lead to the presence of Candida sp. in the urine of catheter users, as identified in this study, include the foods and beverages consumed, medications taken, gender, humidity around the catheter area, and the duration of catheter use, all of which can influence the growth of Candida sp. fungi.